Pulmonary effects of e-liquid flavors: a systematic review. (3rd October 2022) - Effah, Felix; Taiwo, Benjamin; Baines, Deborah; Bailey, Alexis; Marczylo, Tim
ABSTRACT: Electronic cigarettes (ECs) are purported to be tobacco harm-reduction products whose degree of harm has been highly debated. EC use is considered less hazardous than smoking but is not expected to be harmless. Following the banning of e-liquid flavors in countries such as the US, Finland, Ukraine, and Hungary, there are growing concerns regarding the safety profile of e-liquid flavors used in ECs. While these are employed extensively in the food industry and are generally regarded as safe (GRAS) when ingested, GRAS status after inhalation is unclear. The aim of this review was to assess evidence from 38 reports on the adverse effects of flavored e-liquids on the respiratory system in both in vitro and in vivo studies published between 2006 and 2021. Data collected demonstrated greater detrimental effects in vitro with cinnamon (9 articles), strawberry (5 articles), and menthol (10 articles), flavors than other flavors. The most reported effects among these investigations were perturbations of pro-inflammatory biomarkers and enhanced cytotoxicity. There is sufficient evidence to support the toxicological impacts of diacetyl- and cinnamaldehyde-containing e-liquids following human inhalation; however, safety profiles on other flavors are elusive. The latter may result from inconsistencies between experimental approaches and uncertainties due to the contributions from other e-liquid constituents. Further, the relevance of the concentration ranges to human exposure levels is uncertain. Evidence indicates that an adequately controlled and consistent, systematic toxicological investigation of a broad spectrum of e-liquid flavors may be required at biologically relevant concentrations to better inform public health authorities on the risk assessment following exposure to EC flavor ingredients.